Фенологічні аспекти розвитку видів декоративних трав’янистих ліан в умовах Лісостепу України - Pavlenko, L.L.; Mashkovska, S.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The timing of the onset and duration of the main phenological phases of development (stairs, budding, bloom, fruiting) species of ornamental herbaceous vines at growing using seedlings or sowing in the Forest-Steppe of Ukraine are determined. Phenospectrums development of species of herbaceous vines is compiled. Among the studied species we selected phenogroups at the beginning and the duration of flowering: early blooming with intermediate flowering period, early blooming with a long flowering period, average flowering with a long flowering period, late blooming with a short flowering period, late blooming with intermediate flowering period. The duration of decorative period when used seedlings or at sowing is determined. Recommendations concerning the method of cultivation of species of herbaceous lianas in Forest-Steppe of Ukraine depending on the purpose of their use (decorative landscaping or seed production) are given.